2021
DOI: 10.1038/s41598-021-00567-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the origin, genetic structure and demographic history of the common pheasant (Phasianus colchicus) in the introduced European range

Abstract: The common pheasant, a game species widely introduced throughout the world, can be considered as an ideal model to study the effects of introduction events on local adaptations, biogeographic patterns, and genetic divergence processes. We aimed to assess the origin, spatial patterns of genetic variation, and demographic history of the introduced populations in the contact zone of Central and Southeast Europe, using mitochondrial DNA control region sequences and microsatellite loci. Both types of molecular mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…On the other hand, in the feathers of birds of prey from Finland and Pakistan, concentrations of Cd were two times higher, Pb was very diverse, but also higher, and Zn and Cr were similar 33 , 56 to Phasianus colhicus feathers. The results obtained by Janayedeh et al 57 on a house crow in the Klang area of the Malay Peninsula, which was characterized by rapid industrial development, the concentration of Pb was 4–6 times higher, Ni almost 10 times higher, and Zn 2 times higher compared to the researched pheasants.Bearing in mind the above results of the conducted analyses and the fact that species of poking in the soil birds lead a sedentary lifestyle by nature 58 , 59 , it seems necessary to compare the results of our research with the same family of birds. Data on pheasants are quite modest in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the feathers of birds of prey from Finland and Pakistan, concentrations of Cd were two times higher, Pb was very diverse, but also higher, and Zn and Cr were similar 33 , 56 to Phasianus colhicus feathers. The results obtained by Janayedeh et al 57 on a house crow in the Klang area of the Malay Peninsula, which was characterized by rapid industrial development, the concentration of Pb was 4–6 times higher, Ni almost 10 times higher, and Zn 2 times higher compared to the researched pheasants.Bearing in mind the above results of the conducted analyses and the fact that species of poking in the soil birds lead a sedentary lifestyle by nature 58 , 59 , it seems necessary to compare the results of our research with the same family of birds. Data on pheasants are quite modest in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…For the locprior model-based analyses, we stratified the 120 km stretch of Ganges river in the study area into five continuous blocks (each block length ~24 km) based on earlier recorded swamp deer movement patterns in this landscape (Paul et al 2021). The optimal value of K was assessed using the "Evanno" method in STRUCTURE HARVESTER web version (Earl and vonHoldt 2012).The individuals were sorted as "pure" or "admixed" based on 70% ancestry coefficient threshold values (Ashrafzadeh et al 2021). We also used another Bayesian clustering approach implemented in program GENELAND version 4.0.3 (Guillot et al 2005) to assess spatial patterns of genetic structure without assuming admixture (Guillot et al 2005;De et al 2021).…”
Section: Population Structure Detectionmentioning
confidence: 99%
“…Ammotragus lervia is native to North Africa and established in Croatia, Czechia, Italy and Spain following intentional introductions for hunting purposes (Šprem et al 2020). Phasianus colchicus, partly native to Europe, has a long history of introductions and re-introductions with populations established across the continent (Ashrafzadeh et al 2021). Both A. lervia and P. colchicus are highly adaptable and plastic in their use of available food resources, resulting in their distribution expanding rapidly (Hoodless et al 2001;Šprem et al 2020).…”
Section: Trial Screeningsmentioning
confidence: 99%
“…It has been observed that populations of P. colchicus in Croatia have been declining for the past 30 years. However, intended population reinforcements with captive-bred individuals may have negatively affected population size by outbreeding depression, introduction and fast spread of diseases and parasites from birds introduced from foreign sources (Ashrafzadeh et al 2021). As a result, it seems that further population expansion of this species is not to be expected under current conditions.…”
Section: Trial Screeningsmentioning
confidence: 99%